Mortality and immunological indicators of men who have sex with men living with HIV on antiretroviral therapy: a 10-year retrospective cohort study in Southern China - Huaxiang Lu; Huanhuan Chen; Shujia Liang; Yuhua Ruan; He Jiang; Jinghua Huang; Guangjie Tan; Xiuling Wu; Jianjun Li; Chen Gong; Qiuying Zhu; Guanghua Lan (BMC Infectious Diseases)
Abstract Background The proportion of people living with HIV (PLHIV) in Guangxi who are men who have sex with men (MSM) increased rapidly to nearly 10% in 2023; notably, over 95% of this particular population is currently receiving antiretroviral therapy (ART). This study aimed to describe the survival of MSM PLHIV, depict the characteristics and trends of changes in CD4+ T cell counts, CD4+/CD8+ T cell ratio, and viral load, and explore immunological indicators that may be related to mortality during different stages of treatment. Methods Immunological indicators of MSM PLHIV receiving ART were extracted and categorized into baseline, mid-treatment, and last values. These were then incorporated into the Cox models in the form of repeated measurements to evaluate the associations (Adjusted-hazard ratios, aHRs) and 95% confidence intervals (95% CIs) of these immunological indicators with mortality at different stages. Results A total of 5,642 patients who met the criteria were enrolled in the study, and 160 died, representing a mortality of 2.8%. The first, median, and last values of the CD4+ count and the CD4+/CD8+ ratio in surviving patients were significantly greater than the corresponding values in nonsurviving patients (P < 0.001). Except for the first viral load (P = 0.379), the median and last viral loads of the former were significantly lower than those of the latter (P < 0.001). In Cox model, with 2,144 cases, immunological indicators of increased mortality risk included a baseline CD4+ count below 200 cells/µL (aHR: 4.58, 95% CI: 2.28–9.19), a median (aHR: 8.46, 95% CI: 3.05–23.46), and a final (aHR: 4.43, 95% CI: 1.06–18.45) ratio below 0.7 and a median (aHR: 9.47, 95% CI: 4.02–22.35) and final (aHR: 14.46, 95% CI: 4.50–46.50) viral load 100,000 copies/mL and above. Conclusions Mortality among MSM PLHIV on ART in Guangxi is relatively low, and both high viral loads and low CD4+/CD8+ T cell ratios during treatment and at recent follow-up are strongly predictive of a serious prognosis and should be closely monitored.